2014
DOI: 10.2337/dc14-0398
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exenatide, Sitagliptin, or Glimepiride on β-Cell Secretory Capacity in Early Type 2 Diabetes

Abstract: OBJECTIVEAgents that augment GLP-1 effects enhance glucose-dependent β-cell insulin production and secretion and thus are hoped to prevent progressive impairment in insulin secretion characteristic of type 2 diabetes (T2D). The purpose of this study was to evaluate GLP-1 effects on β-cell secretory capacity, an in vivo measure of functional β-cell mass, early in the course of T2D.RESEARCH DESIGN AND METHODSWe conducted a randomized controlled trial in 40 subjects with early T2D who received the GLP-1 analog ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 39 publications
0
32
0
Order By: Relevance
“…Similarly, in the GetGoal-M (27) and GetGoal-S (28) studies, lixisenatide reduced 2-hour postprandial glucagon in response to a meal test after 24 weeks of treatment during which it was added to metformin and sulfonylurea with or without metformin, respectively (probably through its effects on gastric emptying). In contrast, Gudipaty et al (29) reported that indices of the glucagon response to arginine stimulation were unchanged after 6 months of treatment with exenatide (n ϭ 14) or sitagliptin (n ϭ 12), although they were increasedbythesulfonylureaglimepiride(nϭ14),whichserved as an active comparator. Against this background, the current study extends the literature though the serial measurement of 5-point glucagon profiles (0, 30, 60, 90, and 120 minutes) in response to an oral glucose challenge on 5 occasions across 48 weeks of treatment with either liraglutide or placebo.…”
Section: Discussionmentioning
confidence: 88%
“…Similarly, in the GetGoal-M (27) and GetGoal-S (28) studies, lixisenatide reduced 2-hour postprandial glucagon in response to a meal test after 24 weeks of treatment during which it was added to metformin and sulfonylurea with or without metformin, respectively (probably through its effects on gastric emptying). In contrast, Gudipaty et al (29) reported that indices of the glucagon response to arginine stimulation were unchanged after 6 months of treatment with exenatide (n ϭ 14) or sitagliptin (n ϭ 12), although they were increasedbythesulfonylureaglimepiride(nϭ14),whichserved as an active comparator. Against this background, the current study extends the literature though the serial measurement of 5-point glucagon profiles (0, 30, 60, 90, and 120 minutes) in response to an oral glucose challenge on 5 occasions across 48 weeks of treatment with either liraglutide or placebo.…”
Section: Discussionmentioning
confidence: 88%
“…Of these, 613 studies were excluded on the basis of title and abstract, leaving 35 studies for further assessment (Figure ). Eighteen studies ( n = 4911) met our inclusion criteria and were included in the analysis (Figure ), 13 were RCTs comparing a GLP‐1 agonist to a DPP‐4 inhibitor and 5 were interventional studies evaluating change in HbA1c and weight following a switch from DPP‐4 inhibitor to GLP‐1 agonist …”
Section: Resultsmentioning
confidence: 99%
“…The GPA test followed established methodology for evaluation of β-cell secretory capacity and sensitivity to glucose (1113). At 0700 h, one catheter was placed in an antecubital vein for infusions, and one catheter was placed in a distal forearm or hand vein for blood sampling, with the hand placed in a heating pad to promote arterialization of the venous blood.…”
Section: Methodsmentioning
confidence: 99%
“…Estimation of the proinsulin-to-C-peptide ratio within the secretory granules of the β-cell is most reliable after acute stimulation of secretion (19); therefore, we examined the proinsulin secretory ratio (PISR) in response to each injection of arginine from the respective acute proinsulin:C-peptide responses to arginine (12,18). Plasma glucose at which half-maximal insulin secretion is achieved (PG 50 ) was calculated to assess β-cell sensitivity to glucose as previously described (1113). Insulin sensitivity (M/I) was determined by dividing the mean glucose infusion rate required during the 230 mg/dL glucose clamp (M) by the mean prestimulus insulin level (I) between 40 and 45 min of the glucose infusion (12).…”
Section: Methodsmentioning
confidence: 99%